Perancangan Interior Creative Center untuk Anak Down Syndrome di Surabaya - Florensia Febriany; Laksmi Kusuma Wardani; M. Taufan Rizqy (Intra, 2018)
Down Syndrome is a condition of underdevelopment physical and mental condition in children resulting from the failure of a pair of chromosome 21 (trisomy 21) to separate from each other during the division. This condition caused physical and intelligence abnormalities of children with down syndrome, resulting negative discrimination and stigma from people around the community. In fact, children with down syndrome have a wide range of talent and have potential achievements in creativity. Children with down syndrome can be taught and trained with various therapies in order to have a supportive physical condition for self-sufficient living. Through the existing problems, a facility with an interior that have the ability to train for self-sufficient living and creativity development for children with down syndrome is required. The concept of Healing Environment is applied to the design with the implementation on activities (music class, cooking class, snoezelen therapy, etc) and interior design within the important aspects (noise control, privacy, color, texture, etc). Environment that supports healing can provide comfort to children so it will speed up the process of adaptive behavior that is useful for understanding in doing their activities independently (self-sufficient living).